Integrity and life estimation of turbine runner cover in a hydro power plant - A. Sedmak; S. Bosnjak; M. Arsic; S.A. Sedmak; Z. Savic (Fracture and Structural Integrity)
This paper presents integrity and life estimation of turbine runner cover in a vertical pipe turbines, Kaplan 200 MW nominal output power, produced in Russia, and built in six hydro-generation units of hydroelectric power plant „Đerdap 1” in Serbia. Fatigue and corrosion-fatigue interaction have been taken into account using experimentally obtained material properties, as well as analytical and numerical calculations of stress state, to estimate appropriate safety factors. Fatigue crack growth rate, da/dN, was also calculated, indicated that internal defects of circular or elliptical shape, found out by ultrasonic testing, do not affect reliable operation of runner cover.